A Literature Review of Academic Interventions for College Students With Learning Disabilities. (August 2018) - Zeng, Wen; Ju, Song; Hord, Casey
The number of students with learning disabilities (LD) enrolling in postsecondary education has increased rapidly over the past decade. It is imperative to investigate what interventions have been used to assist students with LD in achieving academic success. To examine the interventions currently used to support students with LD in postsecondary education, the authors reviewed the relevant literature from 2000 to 2016. Four primary types of interventions were identified from 12 articles: assistive technology, direct assistance, strategy instruction, and comprehensive support program. The findings indicate that the student-centered approach is an important characteristic of current academic interventions for students with LD in postsecondary education. The authors also provide implications for researchers and practitioners for improving postsecondary interventions on students with LD.